Objective Diagnosis of Multidirectional Instability in Adolescent Patients Based on Glenohumeral Joint Capsule Dimensions on MR Analysis. Issue 5 (31st May 2022) - Yoder, Mason; Veerkamp, Matthew; McDonald, Colin; Parikh, Shital N.
Background: Multidirectional Instability (MDI) of shoulder in adolescents is a clinical diagnosis and there are no defined objective criteria to validate the diagnosis. Most patients with MDI have no identifiable labral or capsular tear pattern on MR imaging. Purpose: To identify objective criteria for MDI diagnosis in adolescent patients based on glenohumeral capsular dimensions on MR imaging. Methods: In a comparative retrospective study, the clinical records and MR arthrogram of adolescent patients treated for shoulder instability at our center between 2008 and 2019 were reviewed. Twenty-four patients treated for MDI were age-matched to 25 patients treated for Bankart tears. The width and depth of the rotator interval and multiple linear dimensions of the glenohumeral capsule were measured on sagittal-oblique MR arthrography sequences, after controlling for glenoid size. These dimensions were compared between the 2 groups using Student's t-test. Power analysis showed a sample size of 16 in each group to be sufficient to detect 5 mm difference in average capsular dimension of 20 mm (power 0.8). Results: 24 patients (28 shoulders) 20 females, 4 males were in the MDI group; average age at time of surgery was 15.2 years (range, 8-20 yrs). The Bankart group consisted of 25 patients (27 shoulders), 9 females, 16 males; average age at time of surgery was 15.4 years (range, 11-18 yrs). The rotator interval depth was significantly greater in the MDI group than the Bankart group (MDI 8.5mm; Bankart 6.1mm) (p <0.01). The inferior, posteroinferior, and posterior dimensions (posterior-inferior quadrant, 3 to 6 o'clock position for left shoulder) of the glenohumeral joint capsule were significantly greater in the MDI group (inferior 24.5mm; posteroinferior 26.4mm, posterior 22.5mm) than in the Bankart group (inferior 20.4mm, posteroinferior 21.9mm, posterior 19.3mm) (p <0.01). Rotator interval width and all other capsular dimensions showed no statistically significant difference between the 2 groups. Conclusion: The depth of the rotator interval and dimension of the glenohumeral joint capsule in the posteroinferior quadrant on MR arthrography were significantly greater in adolescent patients with MDI. This is the first study to objectively quantify capsular volume in adolescent patients with MDI. This information needs to be further validated in prospective fashion and compared to normal capsular dimensions to calculate cut-off values for MDI diagnosis on MR analysis. Figure 1. Sagittal oblique view of the glenohumeral capsule of an adolescent patient with MDI. Line A - Anterior dimension. Line AI - Anteroinferior dimension. Line P - Posterior dimension; Line PI - Posteroinferior dimension; Line I - Inferior dimension; Point S - Superior pole, Point X – Center of glenoid. Table 1. Glenohumeral joint capsule measurements